2012
DOI: 10.1111/j.1365-2222.2012.04006.x
|View full text |Cite
|
Sign up to set email alerts
|

IL‐17 eliminates therapeutic effects of oral tolerance in murine airway allergic inflammation

Abstract: These data suggest that IL-17 may inhibit the induction of tolerance to antigen through, at least in part augmenting IL-6 production, thereby suppressing the expansion of Treg cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Increased levels of pro-inflammatory cytokines in BALF of OVA-sensitized animals were observed in reports, such as IL-1β, IL-6, IL-17 and TNF-α [43][46]. In the current study, we analyzed the levels of TNF-α and IL-6 in BALF to further evaluate the inflammation in lung.…”
Section: Discussionmentioning
confidence: 82%
“…Increased levels of pro-inflammatory cytokines in BALF of OVA-sensitized animals were observed in reports, such as IL-1β, IL-6, IL-17 and TNF-α [43][46]. In the current study, we analyzed the levels of TNF-α and IL-6 in BALF to further evaluate the inflammation in lung.…”
Section: Discussionmentioning
confidence: 82%
“…The expression of VEGF and VEGFR in asthma patients increased accompanied by an increased number and size of blood vessels in asthmatic airways [63]. Interleukin-(IL-) 17 may inhibit the induction of tolerance to antigen through inducing IL-6 production, thereby suppressing the expansion of Foxp3-positive regulatory T (Treg) cells [64]. IL-5 is directly involved in recruiting eosinophils to the lung.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, AHR and allergic inflammation were ameliorated through oral antigen-mediated induction of gut Treg cells, inhibited by endogenous and exogenous IL-17 [15] . Oral administration of ATRA with OVA was thought to induce gut Treg cells, which presumably moved to the lung after the antigen challenges.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that both transfer of T helper (Th) 17 cells or administration of IL-17 in the induction phase of oral tolerance abolished the therapeutic effects of oral tolerance by upregulating IL-6 production in Peyer's patch (PP) in a murine asthma model [15] . The vitamin A metabolite, retinoic acid (RA), has also been reported to enhance the expression of α4β7 integrin and C-C chemokine receptor type 9 on T cells upon activation, imprinting them with gut tropism [16] .…”
Section: Introductionmentioning
confidence: 99%